Penerapan Metode Compost Bag sebagai Media Edukasi Efektif dalam Pengelolaan Sampah Organik di SD Negeri 2 Batuan Kaler - Helmy Syakh Alam; Anak Agung Gede Adi Mega Putra; Ni Putu Reina Savitri; Silvia Levanaries; Atika Dwi Afsari; Ni Putu Ayu Widya Pratiwi; I Gusti Ayu Cessa Jacinda (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to analyze the implementation of the compost bag method as an educational medium to improve students' understanding of organic waste management at SD Negeri 2 Batuan Kaler. The main problems identified were students' low awareness and skills in sorting and processing organic waste, as well as the limited capacity of the existing waste storage facility (teba modern). The method used was a descriptive qualitative approach with a Design Thinking framework. The compost bag method was implemented through hands-on learning activities, where students were directly involved in collecting, sorting, and composting organic waste using compost bags. The results showed an improvement in students' understanding, indicated by an increase in the average pre-test score from 87.71 to 95.71 in the post-test. In addition, there was a reduction of organic waste volume by 400 kg, from 1,177.5 kg to 777.5 kg after the composting process. The compost bag method was also proven to be practical, cost-effective, and easy to implement at the elementary school level. Therefore, the compost bag method can serve as an effective and sustainable environmental education medium for organic waste management in elementary schools.